Quo Vadis the Legal Politics of New Province Formation: Balancing Political Interests and Accelerating Welfare Achievements - Halim, Muhammad; Nurdin, Boy (Journal of Social Science, 2024)
This research discusses the dynamics of new province formation in Indonesia from the perspective of political, social, and economic factors. The formation of new provinces aims to enhance public services, strengthen regional identities, and promote local economic growth. However, this process also presents challenges, such as the potential for social conflict, resource allocation issues, and difficulties in governance management. Political factors, such as regional autonomy policies and the role of political elites, influence the decisions regarding regional expansions, while ethnic identities and community participation are crucial in the social context. In terms of economics, the potential for natural resources and challenges in regional financial management are key concerns. In conclusion, the success of establishing new provinces relies on implementing inclusive and sustainable policies that involve the community in decision-making processes and enhance the capacities of local governments to create welfare and stability